2018
DOI: 10.3390/molecules23030517
|View full text |Cite
|
Sign up to set email alerts
|

Aloin Suppresses Lipopolysaccharide-Induced Inflammatory Response and Apoptosis by Inhibiting the Activation of NF-κB

Abstract: Numerous herbal-derived natural products are excellent anti-inflammatory agents. Several studies have reported that aloin, the major anthraquinone glycoside obtained from the Aloe species, exhibits anti-inflammatory activity. However, the molecular mechanism of this activity is not well understood. In this report, we found that aloin suppresses lipopolysaccharide-induced pro-inflammatory cytokine secretion and nitric oxide production, and downregulates the expression of tumor necrosis factor alpha (TNF-α), int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
(49 reference statements)
2
29
1
Order By: Relevance
“…Luo et al ( 35 ) demonstrated that aloin attenuated LPS-induced NF-κB transcriptional activity by inhibiting its upstream kinase p38 MAPK and mitogen- and stress-activated protein kinase-1. However, the results of the present study demonstrated that aloin pretreatment had no effect on LPS-induced p38 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al ( 35 ) demonstrated that aloin attenuated LPS-induced NF-κB transcriptional activity by inhibiting its upstream kinase p38 MAPK and mitogen- and stress-activated protein kinase-1. However, the results of the present study demonstrated that aloin pretreatment had no effect on LPS-induced p38 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Aloin (ALO) is a bioactive component that is extracted from aloe vera. It has been reported to have anti-inflammatory, 1,2 anti-oxidant, 3 and anti-tumour effects. 4,5 In addition, ALO has been reported to inhibit proliferation and induce the apoptosis of various tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In addition, ALO has been reported to inhibit proliferation and induce the apoptosis of various tumour cells. 1,5,6 However, the molecular mechanism(s) underlying ALO's anti-cancer activity remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that inflammatory cells play an important role in neurodegenerative diseases via release of various pro‐inflammatory molecules (Calabrese et al., ). For example, NO is a labile molecule that has been associated with numerous pathological processes, and it is produced by iNOS, which is locally secreted by inflammatory stimuli (Luo et al., ). In addition, the pro‐inflammatory cytokines IL‐6, TNF‐α and IL‐1β are potent enhancers of neuroinflammatory reactions and are involved in demyelination and neuronal damage (Yu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NO is a labile molecule that has been associated with numerous pathological processes, and it is produced by iNOS, which is locally secreted by inflammatory stimuli (Luo et al, 2018). In addition, the pro-inflammatory cytokines IL-6, TNF-and IL-1 are potent enhancers of neuroinflammatory reactions and are involved in demyelination and neuronal damage (Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%